2020
DOI: 10.7717/peerj.10517
|View full text |Cite
|
Sign up to set email alerts
|

Climatic niche comparison between closely related trans-Palearctic species of the genusOrthocephalus(Insecta: Heteroptera: Miridae: Orthotylinae)

Abstract: Previously climatic niche modelling had been studied for only a few trans-Palearctic species. It is unclear whether and to what extent those niches are different, and which climatic variables influence such a wide distribution. Here, environmental niche modelling is performed based on the Worldclim variables using Maxent for eight species of the genus Orthocephalus (Insecta: Heteroptera: Miridae: Orthotylinae). This group belongs to one of the largest insect families and it is distributed across Palearctic. Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 60 publications
(72 reference statements)
3
21
0
Order By: Relevance
“…Third, it was shown that the ecological niches of the trans-Palearctic species are similar to each other and to those of widespread species, which are distributed mostly in Europe (O. coriaceus) and Northeast Asia (O. funestus) (Namyatova, 2020). At the same time, the niches of the trans-Palearctic species are less similar to those of more local species inhabiting the Mediterranean areas of the western Palearctic (O. fulvipes and O. proserpinae).…”
Section: Animal Ecologymentioning
confidence: 95%
See 3 more Smart Citations
“…Third, it was shown that the ecological niches of the trans-Palearctic species are similar to each other and to those of widespread species, which are distributed mostly in Europe (O. coriaceus) and Northeast Asia (O. funestus) (Namyatova, 2020). At the same time, the niches of the trans-Palearctic species are less similar to those of more local species inhabiting the Mediterranean areas of the western Palearctic (O. fulvipes and O. proserpinae).…”
Section: Animal Ecologymentioning
confidence: 95%
“…These taxa must be able to adjust to different conditions, and they are very likely to be welladapted to the most common conditions in the regions, which include the largest biomes and climate zones. In the previous paper, based on the climatic data only, it was shown that four closely related trans-Palearctic Orthocephalus species are differently adapted to the climatic conditions, and their ecological niches are not identical (Namyatova, 2020). However, the species' preferences for the particular biomes and climate zones were not studied.…”
Section: Animal Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…The bias introduced by the difference between occurrence collection and background sampling can be avoided by ensuring that the background sample reflects the same bias as the presence data. Some studies show that biased background sampling can lead to much better predictive performance than random background sampling (Kramer‐Schadt et al, 2013; Namyatova, 2020; Phillips & Dudík, 2008; Phillips et al., 2009). This option of sampling biased background data is implemented in MaxEnt software by adding a bias grid, with which the cell values reflect sampling effort and give a weight to choose background data (Fourcade et al., 2014).…”
Section: Methodsmentioning
confidence: 99%